2015
DOI: 10.1371/journal.pone.0141667
|View full text |Cite
|
Sign up to set email alerts
|

Culicoides Species Communities Associated with Wild Ruminant Ecosystems in Spain: Tracking the Way to Determine Potential Bridge Vectors for Arboviruses

Abstract: The genus Culicoides Latreille 1809 is a well-known vector for protozoa, filarial worms and, above all, numerous viruses. The Bluetongue virus (BTV) and the recently emerged Schmallenberg virus (SBV) are responsible for important infectious, non-contagious, insect-borne viral diseases found in domestic ruminants and transmitted by Culicoides spp. Both of these diseases have been detected in wild ruminants, but their role as reservoirs during the vector-free season still remains relatively unknown. In fact, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 54 publications
5
40
1
Order By: Relevance
“…There, serology was negative for wild and domestic ruminants in 2011. The current putative SBV vectors of the Obsoletus complex were described to be in close contact with wild and domestic ruminants in the same mountainous region (Talavera et al., ). Our results are in agreement with those obtained in northern and central Europe where SBV was primarily detected in pools of the Obsoletus complex (reviewed in Balenghien et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…There, serology was negative for wild and domestic ruminants in 2011. The current putative SBV vectors of the Obsoletus complex were described to be in close contact with wild and domestic ruminants in the same mountainous region (Talavera et al., ). Our results are in agreement with those obtained in northern and central Europe where SBV was primarily detected in pools of the Obsoletus complex (reviewed in Balenghien et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The virus spread rapidly north beyond the Arctic Circle, and occurred in high prevalence in tested animals [15]. However, it was not known if the virus did circulate (in 2012) or still is circulating in wildlife ruminant populations, and if they could act as reservoirs for the virus [16]. …”
Section: Introductionmentioning
confidence: 99%
“…In woodlands, higher abundance of Culicoides than expected considering the distance of the sampling sites to the farm, was observed, although this varied according to species (Rigot et al, 2013). Talavera et al (2015) showed that C. imicola and C. obsoletus/C. scoticus are found either in farms and in natural areas were wild ruminants species are the main hosts.…”
Section: Culicoides Species Implicated In Btv Transmissionmentioning
confidence: 79%
“…In the study by Talavera et al. (), samplings were conducted in Spain in areas inhabited by different wild ruminant species. The most abundant vector species were C. imicola and C. obsoletus/C.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation